2007
DOI: 10.1037/0012-1649.43.3.778
|View full text |Cite
|
Sign up to set email alerts
|

Toward a developmental psychology of Sehnsucht (life longings): The optimal (utopian) life.

Abstract: The topic of an optimal or utopian life has received much attention across the humanities and the arts but not in psychology. The German concept of Sehnsucht captures individual and collective thoughts and feelings about one's optimal or utopian life. Sehnsucht (life longings; LLs) is defined as an intense desire for alternative states and realizations of life. Presenting a first effort at capturing this phenomenon, the authors conceptualize LLs as composed of 6 interrelated core characteristics: (a) utopian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(109 citation statements)
references
References 83 publications
8
93
2
4
Order By: Relevance
“…The bittersweet essence of Sehnsucht was perhaps a significant reason the word was nominated as the third-most-beautiful word in the German language (Deutscher Sprachrat, 2004)! 2 Recent research has addressed the extent to which Sehnsucht is functional for an individual (Scheibe, Freund, & Baltes, 2007), focusing in particular on major life longings (e.g., physical well-being, romantic partnerships). Self-report data from individuals of various ages revealed that Sehnsucht provides individuals with a sense of directionality in life and helps them cope with their perceived imperfections (Scheibe et al, 2007).…”
Section: Lifespanmentioning
confidence: 99%
See 1 more Smart Citation
“…The bittersweet essence of Sehnsucht was perhaps a significant reason the word was nominated as the third-most-beautiful word in the German language (Deutscher Sprachrat, 2004)! 2 Recent research has addressed the extent to which Sehnsucht is functional for an individual (Scheibe, Freund, & Baltes, 2007), focusing in particular on major life longings (e.g., physical well-being, romantic partnerships). Self-report data from individuals of various ages revealed that Sehnsucht provides individuals with a sense of directionality in life and helps them cope with their perceived imperfections (Scheibe et al, 2007).…”
Section: Lifespanmentioning
confidence: 99%
“…2 Recent research has addressed the extent to which Sehnsucht is functional for an individual (Scheibe, Freund, & Baltes, 2007), focusing in particular on major life longings (e.g., physical well-being, romantic partnerships). Self-report data from individuals of various ages revealed that Sehnsucht provides individuals with a sense of directionality in life and helps them cope with their perceived imperfections (Scheibe et al, 2007). However, similar to our own findings on the influence of regret on well-being (Roese et al, 2008), an excess of Sehnsucht is associated with reduced well-being.…”
Section: Lifespanmentioning
confidence: 99%
“…As agent-selves, we plan future performances to live out the choices we have made and fulfi ll our most important goals. Our future plans-short-term and long-term, mundane and exalted-may be captured in the personal strivings (Emmons, 1986), personal projects (Little, 1999), and life longings (Schiebe, Freund, & Baltes, 2007) into which we invest our psychic energies. Like a strategic investment banker, the I chooses to infuse capital into those strivings, projects, and longings that promise a good return in the future.…”
Section: Life Goals Possible Selves and Identitymentioning
confidence: 99%
“…However, earning a university degree is still an important achievement and, especially for ''first-generation'' graduates, often leads to positive developmental outcomes [e.g., Pascarella, Pierson, Wolniak, & Terenzini, 2004]. In other cases, however, remaining in the unexposed phase and not pursuing alternate pathways suggested by unexpected events might result in personal regret, even Sehnsucht [Scheibe, Freund, & Baltes, 2007] or intense longing.…”
Section: Phase 1: Unexposedmentioning
confidence: 99%